Pengaruh Disiplin Kerja, Motivasi Kerja, dan Lingkungan Kerja terhadap Kinerja Pegawai Dinas PUPR di Kota Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The spot of this analyze is to close the impact of work teach, work inspiration and work environment on the execution of PUPR workers in Denpasar City. Everyone in this consider were all ASN and non-ASN workers at the PUPR Division of Denpasar City with a sum to of 124 ASN workers and 132 non-ASN workers with a sum to preliminary of 256 respondents who were picked utilizing the soaked test method. Information arrangement was assisted through understanding, interviews, documentation, making consider, outlines. The information appraisal strategy utilized in this look at is the way assessment framework. Considering the investigate happens, it might be seen that: Work instruct contains a positive and tremendous impact on delegate execution. Work inspiration contains a positive and indispensable impact on delegate execution. The work environment incorporates a positive and essential impact on laborer execution. Work teach, work inspiration, and working environment noteworthily influence worker execution. Looking at the inspect happens as expected, inside the future the Denpasar City PUPR Benefit ought to apply extreme approvals to workers who hurt the guidelines. This is a large part of the time essential to do so designates don't set out to hurt existing norms inside the association